Effect of mercury concentration and operating parameters to mercury removal using portable mercury removal rig (PMRR) for petrochemical wastewater - Zulkiflee, Sulaiman (2013)
Mercury is a type of heavy metal that naturally occurs on the earth crust. It can be found in soil, rocks and sea. It can be release to the environment through natural processes such as rock erosion, soil decomposition or volcanoes eruptions. It also released to the environment by human activities such as mining and industrial processes from petrochemical and chlor-alkali industries. Mercury is usually used in the thermometer, thermostat, barometer, bulbs, dental amalgams and switches. Mercury is one of the hazardous chemical elements that exist on the earth. It can attack human central nervous system, kidney, lungs and other body systems. Thus the objective of this research is to study on the mercury concentration and operating parameters to mercury removal using Portable Mercury Removal Rig (PMRR) for petrochemical wastewater. The mercury removal process was conducted under different inlet pressure; 5, 10 and 23 psig, different inlet concentration; 2, 4, 6 and 8 ppm, different pH and lastly using different absorbent; extruded activated carbon (EAC), granular activated carbon (GAC) and ion exchange (IE) resins. As the result, the best inlet pressure was 5 psig while the best inlet concentration is from 2-4 ppm. The best absorbent is ion exchange because of faster mercury removal mechanism while low pH is preferred for operating parameter of PMRR. As the conclusion, the mercury removal is increased as the pressure, inlet concentration and pH value are decreased.